The hypothetical model of professional burnout in the Ukrainian Armed Forces - MYKOLAICHUK, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Restoring the mental health of servicemen, regarded as a crucial strategic resource of the Armed Forces, is a highly relevant issue today. Professional burnout, as a factor that negatively affects efficiency, productivity, and the quality of combat missions, is increasingly drawing the interest of military professionals worldwide. This article focuses on analyzing contemporary theories of burnout, exploring scientific works on various aspects of this condition, which is essential for developing corrective programs.The purpose of the article is to construct a hypothetical model of burnout, considering the causal relationships inherent to the phenomenon under study, to analyze related concepts, characteristics, and classifications used to describe processes and consequences, to identify the primary components, and to substantiate the specifics of the formation and development of the syndrome in a particular group of individuals.Methods. The study employed several methods: abstraction, analysis, and synthesis of scientific literature, allowing for an examination of burnout both historically and currently, exploration of psychological experiences related to this problem, observation of military personnel's professional activities, and generalization and specification to form conclusions.Results. The study examined the theoretical basis of this phenomenon, considered the specifics of burnout development in military personnel, and identified the causes of this phenomenon. In addition, a hypothetical model of military burnout, specifically adapted to the context of military service and considering the unique stresses and challenges of today, was proposed, identifying its key components and their development dynamics over time.Conclusions. The issue of studying the problem of emotional burnout today is quite controversial and causes discussions, as it correlates with comorbid conditions such as depression, anxiety, stress disorders, etc. The proposed model accounts for the peculiarities of this phenomenon, the individual characteristics of each serviceman, and the influence of socio-psychological factors on the risk of servicemen's burnout, allowing for the development of effective strategies for preventing and managing this phenomenon.
Keywords: burnout; Armed Forces; military personnel; hypothetical model; mental health